Dose-dependent effect of bemiparine in patients with oncologically conditioned obstructive jaundice et various disorders of hemostasis - O. O. Tarabrin; O. S. Kushnir (Zaporozhye State Medical University, 2013)
Abstract Over the last decade there is steadily increasing number of patients with obstructive jaundice (OJ) in Ukraine. There is no observed tendency to the decrease of mortality rate due to thrombohemorrhagic syndrome in patients who are operated on mechanical jaundice. It is necessary to consider the prevalence of thrombotic processes over the fibrinolysis processes and consider the activation of platelet aggregation as an additional factor, which participates in providing hypercoagulation. The aim of the study was to analyze the dose-dependent effect of bemiparine in patients with obstructive jaundice (OJ) due to oncological diseases of the hepatobiliary system. 70 patients with decompensated type of reaction to hypoxia were examined using low-frequency vibration piezoelectric hemoviscosymetry (LVPH). Patients of the 1st group (n=34) were getting thromboprophylaxis with bemiparine 2500 U 1 time per day during the week, starting 6 hours after surgery. The 2nd group of high risk of thrombotic complications (n=36) received 3500 U once a day. Рostoperative thrombohemorrhagic complications prevention in patients with OJ should be based on the assessment of the risk of thrombotic complications and the degree of initial hemostasis disorders. Differentiated approach to the hemostasis correction in patients with OJ allows reducing the incidence of thrombosis by 48.2%. Usage of low-frequency piezoelectric hemoviscosymetry method in regular practice allows evaluating the status of all parts of the hemostasis system, which allows reducing the number of thrombohemorrhagic complications in the postoperative period. Dynamics of hemocoagulatory disorders in patients with OJ due to malignant diseases of the hepatoduodenal zone, who received bemiparine for correction of hemostatic system disorders, was characterized by a tendency to normalization of platelet aggregation - decrease of the contact phase coagulation by 35,18% (p <0, 001), the normalization of the coagulation link - decrease of the index of coagulation drive to 37,48% (p <0.001) as well as fibrinolysis activation - increase of the retraction index and clot lysis by 96,73% (p <0.001) during the first 3 days of post-operative treatment. The use of combined and differentiated prevention of postoperative thrombohemorrhagic complications in patients with OJ should be based on the assessment of thrombotic complications risk and the degree of initial hemostasis disorders. In patients groups with high-risk and decompensated type of reaction on a test with two-times local hypoxia of upper limb, higher doses of LMG-bemiparine 3500 U should be used. Introduction of differentiated approach to the hemostasis correction in patients with OJ allows reducing the number of thrombosis cases by 48.2%.